Kesetaraan gender di era globalisasi pada peran perempuan dalam menghadapi era digital - Dahyoko, Wahyu; Anajani, Ayu Giri; Kartika, Eva Dwi; Aisyah, Nur; Saputra, Akmal Hakim; Erni, Sukma (Journals of Indonesian Multidisciplinary Research, 2024)
Women's empowerment in the digital era refers to the role of women in being able to optimize their potential in utilizing information and communication technology in the digital era. The author wrote this article with the aim of knowing the role of women in the era of globalization and how they can take advantage of developments in science in the current era of globalization. This is what makes women's roles increasingly complex. So that women have a big role in the development of digital technology at this time, there are many things that the current generation can do, especially for women, in facing the era of digital technology where the role of women has the potential to work in the digital industry, such as using social media platforms, becoming influencers. in mass media, marketing products online or becoming a beauty vlogger, and there are many more things that women can do in today's digital era.